2010
DOI: 10.1111/j.1439-0426.2010.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in the water, sediment and fish in the Neretva River Delta, Croatia

Abstract: The Neretva River Delta in Croatia is under constant threat of pollution from various sources along the river watercourse, such as the aluminium industry and bauxite mining, intensive agriculture and untreated sewage from towns. The area is also an important fishing ground and food source for the local residents, whereby the suitability of fish for human consumption is always in question. In this paper the presence of arsenic from six sources was analysed: in water, sediment and fish organs (kidneys, liver, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…However, in this study, eels had comparatively higher levels only of Cd, Cr, Na and Se in their muscle, while at the same time the concentrations of As, Cu, Fe, K, Mg, Mn, Mo and Sr were the lowest compared to other analyzed species. Our results are in good agreement with results of Has-Schon et al [ 56 ] and Bukvić et al [ 57 ] for the Neretva River and Rakočević et al [ 45 ] for Skadar Lake, in which eels often had lower concentrations of some elements in comparison to other species. Generally, our results showed that no species had the highest concentrations of all metals ( Table 4 ), indicating that trophic levels and feeding location were not good predictors of element levels, probably because the trophic levels of the analyzed species in this study varied within a relatively narrow range from 2.47 ( P. carp ) to 3.55 ( E. eel ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, in this study, eels had comparatively higher levels only of Cd, Cr, Na and Se in their muscle, while at the same time the concentrations of As, Cu, Fe, K, Mg, Mn, Mo and Sr were the lowest compared to other analyzed species. Our results are in good agreement with results of Has-Schon et al [ 56 ] and Bukvić et al [ 57 ] for the Neretva River and Rakočević et al [ 45 ] for Skadar Lake, in which eels often had lower concentrations of some elements in comparison to other species. Generally, our results showed that no species had the highest concentrations of all metals ( Table 4 ), indicating that trophic levels and feeding location were not good predictors of element levels, probably because the trophic levels of the analyzed species in this study varied within a relatively narrow range from 2.47 ( P. carp ) to 3.55 ( E. eel ).…”
Section: Resultssupporting
confidence: 92%
“…Generally, our results showed that no species had the highest concentrations of all metals ( Table 4 ), indicating that trophic levels and feeding location were not good predictors of element levels, probably because the trophic levels of the analyzed species in this study varied within a relatively narrow range from 2.47 ( P. carp ) to 3.55 ( E. eel ). The highest As values in the flathead grey mullet, which have also been recorded previously [ 55 , 56 , 57 ], could be expected given that marine fish generally have significantly higher concentrations of organic As species in comparison to freshwater species from unpolluted environments [ 58 ]. In addition, IMBI values in the muscles of six fish species (0.130–0.572) also significantly differed between species ( Table 4 ).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Accumulation of As and Cd exceeding the level of the current regulation was observed in the crab shells. The sediment arsenic content in the current crabs’ collection site was recently reported between 18.7 and 47.2 mg kg −1 [ 21 ]; since crabs are bottom-dwelling animals, the relatively high As content in crab shells of 22.5 to 46.1 mg kg −1 was not so surprising. The wind-borne pollution can explain shell cadmium content from a bauxite terminal in the vicinity of the collection site.…”
Section: Resultsmentioning
confidence: 96%
“…Among other factors, the introduction and high incidence of the swim bladder parasite [5]. and pollution from agriculture, upstream industries, and mining [25]. have already been mentioned.…”
Section: Discussionmentioning
confidence: 99%